Seguridad del transporte y satisfacción del turista en el balneario Bellavista Nanay Iquitos 2023 - Panduro Márquez, Ana Isabel (2024)
The objective of this research report was to determine the relationship between transportation safety and tourist satisfaction at the Bellavista Nanay Spa, Iquitos 2023. Where an applied type study was chosen, correlational and descriptive level with a non-experimental design, whose the study population was 1,500 tourists, taking 375 as a sample. A questionnaire was used to collect data. Meanwhile, it was concluded that transportation has a medium level of safety (26%), since there is a lack of variety of cleaning products and the appropriate permits have not always been made visible. First aid kits have also not been seen frequently, but preferential attention has been observed for children, older adults and people with disabilities. For its part, tourist satisfaction is at a medium level (28%), mainly because the restaurant service is considered average. Furthermore, the quality of tourist attractions is also perceived as poor. However, the excellent care and conservation of cultural attractions stands out. Finally, it was determined that there is a significant correlation between the variables, being demonstrated by a coefficient of 0.870 and a significance of 0.000 being statistically significant.